A SYSTEMATIC LITERATURE REVIEW ON FINANCING MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) - Ika, Syahrir (Journal of Social Political Sciences, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in fostering economic growth within a nation. The significance of this role is seen in the impact of MSMEs on various aspects such as employment generation, business capital accumulation, export promotion, poverty reduction, and the mitigation of income inequality. Several studies confirm that it is challenging for MSMEs to grow and develop. The primary challenges encompass constrained financial resources and impediments in securing funding from banking institutions. Various governments across numerous countries provide fiscal support to MSMEs through the provision of guarantees and interest subsidies. This research aims to determine the concept and implementation of program credit using the Systematic Literature Review method. This research found that government intervention in MSME financing programs, both in guarantee subsidy schemes and interest subsidies, varies depending on the business phasing process, business scale, and type of business. The government usually facilitates medium-scale MSMEs with a guarantee subsidy scheme. In the interim, the government provides support to small-scale and micro-scale MSMEs through the implementation of an interest subsidy scheme. Financing MSMEs with an interest subsidy scheme is more effective, but in some cases, guarantee subsidies are more effective. Government intervention is often misdirected because the government in several countries does not yet have credit scoring and certification for MSMEs.